Expectativas positivas com o uso de álcool e o beber se embriagando: Diferenças de gênero em estudo do projeto GENACIS, São Paulo, Brasil - Cavariani, Mariana Braga; de Oliveira, Janaina Barbosa [UNESP]; Kerr-Corrêa, Florence [UNESP]; Lima, Maria Cristina Pereira [UNESP] (FapUNIFESP (SciELO), 2012)
The objective was to investigate expectations towards alcohol use among men and women and the association between these expectations and binge drinking (or heavy episodic drinking). An epidemiological cross-sectional populationbased household survey with a stratified probabilistic sample was conducted in Greater Metropolitan São Paulo, Brazil. Males and females were interviewed (n = 2,083) with the GENACIS questionnaire (Gender, Alcohol, and Culture: an International Study). The dependent variable was binge drinking, and logistic regression models were constructed for each gender, adjusting for age, schooling, and income. All expectations, with the exception of increased ease in talking with one's partner, were associated with binge drinking. The study shows that binge drinking can be associated with expectations towards alcohol use. Understanding such expectations can contribute to the design of effective polices to prevent binge drinking.
Positive expectations towards alcohol use and binge drinking: Gender differences in a study from the GENACIS project, São Paulo, Brazil
Keywords: Alcohol drinking; Alcoholism; Behavior